Fiber orientation evaluation in reinforced composites using digital image correlation and thermal excitation. (1st April 2022) - Spencer, Ryan; Alwekar, Shailesh; Jo, Eonyeon; Hassen, Ahmed Arabi; Kim, Seokpum; Vaidya, Uday
Abstract: A digital image correlation (DIC) nondestructive evaluation (NDE) method for determining fiber orientation in a composite material was developed. Fiber orientation is a crucial factor that influences the mechanical and thermal properties of fiber reinforced composites. By thermally exciting the composite surface, DIC measured the strain difference axial and transverse to the fiber axis to determine fiber orientation. A 2.7x increase in strain transverse to the fiber axis was observed compared to the longitudinal axis. The transverse direction experiences a larger strain of 0.00445 m/m due to the higher thermal expansion in the surrounding polymer matrix than the fiber direction which resists expansion and resulted a 0.00166 m/m strain. DIC provides a full-field qualitative measurement for fiber orientation while maintaining high resolution. This innovative method is in a preliminary stage and has been developed to fill the gap/limitations of complementary NDE methods. Graphical abstract: Image 1 Highlights: Fiber orientation measured by locally heating the composite surface and monitoring the strain response with DIC technique. A thermal strain mis-match was observed along and transverse the fiber axis. Low strain occurs along the fiber axis whereas high strain occurs transverse to the fiber axis due to polymer expansion. Maintaining local heating below the glass transition temperature allows nondestructive fiber orientation measurements.